(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
Goals of governments are usually formulated in the form of public policies, and legislation is an instrument by which political visions and goals are achieved. The creation of new legislation inevitably produces costs and benefits for those to whom the legislation applies as well as for society as a whole. In an effort to make new legislation more cost-effective, governments use a variety of tools to improve the quality of regulations and other acts. Governments that apply various tools to improve the quality of legislation implement the principles of "smart" legislation (better regulation, smart regulation). In such a state of affairs, how can we constructively, using digital tools and procedures when establishing companies via the Internet, ensure simpler, faster and more time and cost-effective starting of economic activity? Is better regulation the result of good legislative instruments and procedures that enable high quality legislation and the rule of law? How will the use of digital tools and procedures in company law bring economic and social benefits to society as a whole? The aim of this paper is to show that by adopting the Directive on the use of digital tools and procedures in company law (2019/1151), the European Union is taking further steps to digitize and modernize company law as a whole, and thus achieve what is at the heart of the European Commission. it is better regulation.